2020
DOI: 10.1039/d0ra02168g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sintering resistance of bimetal/SBA-15 catalysts with promising activity under a low temperature for CO methanation

Abstract: Well-dispersed bimetallic catalysts with confinement effects and strong interaction lead to superior low-temperature activity and excellent thermostability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…For the Ni/SBA-15-I, the smaller Ni particle size indicates that the Ni 2+ was infiltrated and uniformly dispersed into the internal surface of mesopores by using the incipient wetness impregnation method. Moreover, as reported in the literature [39], the Ni/SBA-15 catalyst with Ni loading of 10% was prepared by using the citric acid-assisted impregnation method, and the NiO particle size was about 8.1 nm, which was slightly larger than that of Ni/SBA-15-M-C (6.5 nm) in this work. This result indicated that the physical mixing of Ni(NO 3 ) 2 •6H 2 O and SBA-15 in the presence of citric acid as a complexing agent is an efficient strategy for preparing the Ni-based catalyst with higher dispersion.…”
Section: Structural Properties Of Ni-based Catalystssupporting
confidence: 59%
“…For the Ni/SBA-15-I, the smaller Ni particle size indicates that the Ni 2+ was infiltrated and uniformly dispersed into the internal surface of mesopores by using the incipient wetness impregnation method. Moreover, as reported in the literature [39], the Ni/SBA-15 catalyst with Ni loading of 10% was prepared by using the citric acid-assisted impregnation method, and the NiO particle size was about 8.1 nm, which was slightly larger than that of Ni/SBA-15-M-C (6.5 nm) in this work. This result indicated that the physical mixing of Ni(NO 3 ) 2 •6H 2 O and SBA-15 in the presence of citric acid as a complexing agent is an efficient strategy for preparing the Ni-based catalyst with higher dispersion.…”
Section: Structural Properties Of Ni-based Catalystssupporting
confidence: 59%
“…According to Figure 8(a), the carbon removal process could be divided into three stages: [34] 100-250 °C, 250-550 °C and 550-950 °C. In the low temperature region (100-250 °C), the conversion does not change obviously with the increase of temperature, indicating that carbon deposition oxidation was not involved in the region (Figure (5) and Figure ( 6)). In the medium temperature region (250-550 °C), the conversion curves changed sharply with the increase of temperature, especially for Ni/MgO (0) -Al 2 O 3 , indicating that the carbon removal reaction mainly occurred in this region.…”
Section: Carbon Removal Kineticsmentioning
confidence: 98%
“…Therefore, methanation process requires high activity and well stability for catalyst in such an uneven environment. [4,5] Ni-based catalysts has aroused widespread concerning for their high activity, low cost and easy availability and lots of works have been carried out on it. Studies showed [7,8] that the particle size and dispersity of the active metal, as well as the specific surface area have a great influence on the performance of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…CO methanation, known as the Sabatier reaction, has been recently applied for the production of synthetic natural gas, 1,2 an important process for clean coal utilization. It has been used to remove trace CO for the production of ammonia and fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 With increasing concerns regarding CO 2 utilization in the emission control of greenhouse gases, storage of renewable hydrogen and in life cycle systems in space stations, the study of CO methanation is now even more important. [3][4][5][6] Due to their relatively high activity and relatively low price, oxide-supported Ni catalysts have been extensively applied for CO 2 reforming of methane, 7,8 methane decomposition, 9 and CO 1,2,[10][11][12] and CO 2 methanation. [3][4][5][6] However, carbon formation and sintering cause the deactivation of Ni catalysts for CO methanation.…”
Section: Introductionmentioning
confidence: 99%